The Key Challenges of Organization to Adopt Lean or green practices: A Systematic Literature Review - Puspani, Nissa Syifa (CENTRAL ASIA AND THE CAUCASUS, 2022)
The logistics organization are motivated to improve performance in order to rose the performance and improve organizational performance, especially in terms of effective processes (Wallenburg et al., 2010). Lean management, a derivative of the Toyota Production System, has been trusted and proven to support an organization in improving performance. Meanwhile, each organization's different needs and characteristics will lead to further adoption and adaptation in improving work performance and also environment effect. In order to answer this gap, the author purpose the systematic literature review (SLR) by [1] were carried out. Through the process analysis of articles, the paper determines the key challenges of organization towards lean or green practices and the key point in lean management.